Associations of occupation, job control and job demands with intima-media thickness: The Multi-Ethnic Study of Atherosclerosis (MESA). Issue 5 (8th October 2010) - Fujishiro, Kaori; Diez Roux, Ana V; Landsbergis, Paul; Baron, Sherry; Barr, R Graham; Kaufman, Joel D; Polak, Joseph F; Stukovsky, Karen Hinckley
Abstract : Objectives: Occupation has been linked to cardiovascular disease (CVD) incidence and mortality, but few studies have investigated occupation in relation to early atherosclerotic disease. This study examined associations between various occupational characteristics and carotid artery intima-media thickness (IMT) in a multi-ethnic sample. Methods: The Multi-Ethnic Study of Atherosclerosis (MESA) recruited 6814 adults aged 45–84 years and free of clinical CVD (response rate 60%, 51% female). Questionnaire data were used to determine occupational group (managerial/professional, sales/office, service, blue-collar), psychosocial job characteristics (ie, job demands, job control) and other sociodemographic information. Results: Common carotid artery (CCA)-IMT was greater for blue-collar jobs than for management/professional jobs (mean difference=0.012 mm, p=0.049) after adjustment for age, sex, race, place of birth (US or foreign born) and CVD risk factors. Compared to management/professional jobs, internal carotid artery (ICA)-IMT was greater for sales/office, service and blue-collar jobs (mean difference=0.071 mm, p<0.001; 0.057 mm, p=0.009; and 0.110 mm, p<0.001, respectively) after adjustment for age, sex, race and place of birth. The difference between blue-collar jobs and management/professional jobs remained significant after additional adjustment for CVD risk factors, income and education (mean difference=0.048 mm, p=0.045). Higher levels of control at work were associated with thinner CCA-IMT (mean difference=−0.009 mm, p=0.016, adjusted for age, sex, race and place of birth) but not with ICA-IMT. Job demands had no significant association with IMT. Conclusions: Blue-collar jobs and low levels of job control were associated with the development of subclinical atherosclerosis.